How Social Media Marketing and Online Reviews Influence the Likelihood of Customers Buying Again: The Role of Brand Trust Among Tokopedia Users in Bandung City - Nurharis, Zulfikar; Erpurini, Wala (International Journal of Management Science and Information Technology, 2026)
The rapid growth of the e-commerce sector in Indonesia has intensified competition among online shopping platforms, making customer loyalty and repurchase intention increasingly important for businesses. The decline in Tokopedia’s Top Brand Index indicates challenges in maintaining consumer loyalty and encouraging repeat purchases. This study aims to examine the effect of Social Media Marketing (SMM) and Electronic Word of Mouth (E-WOM) on Repurchase Intention through Brand Trust as a mediating variable among Tokopedia users in Bandung City. This study adopts the Stimulus–Organism–Response (SOR) framework, in which SMM and E-WOM represent external stimuli, Brand Trust represents the consumer’s internal psychological state, and Repurchase Intention represents the behavioral response. A quantitative approach was employed through a survey of 165 Tokopedia users in Bandung City selected using purposive sampling. The data were analyzed using multiple linear regression and the Sobel test with IBM SPSS version 26. The results indicate that both Social Media Marketing and Electronic Word of Mouth have a positive and significant effect on Brand Trust. Furthermore, Brand Trust has a positive and significant effect on Repurchase Intention. The mediation results also demonstrate that Brand Trust mediates the relationship between Social Media Marketing and Electronic Word of Mouth and Repurchase Intention. These findings indicate that effective digital marketing activities and consumer-generated information can strengthen brand trust, which subsequently encourages consumers to repurchase. This study contributes to the application of the SOR framework in the Indonesian e-commerce context and provides practical implications for Tokopedia in developing effective digital marketing strategies and strengthening consumer trust to encourage repeat purchases.
Keywords: Social Media Marketing; Electronic Word of Mouth; Brand Trust; Repurchase Intention; Tokopedia; E-commerce